MEDB-72. MOLECULAR CHARACTERIZATION OF MEDULLOBLASTOMAS IN A SINGLE INSTITUTION. (3rd June 2022) - Tan, Enrica E K; Tan, Mui Li; Kuick, Chik Hong; Yong, Min Hwee; Low, Sharon Y Y; Chang, Kenneth T E; Tan, Char Loo
Abstract: INTRODUCTION: The four molecular groups (WNT, SHH, Group 3 and Group 4) in medulloblastoma have been well established for the past decade. New subgroups within the four principal molecular groups have recently been discovered and recognized by WHO classification of Central Nervous System Tumours (5th edition). Subgroups were reported to have distinct somatic copy-number aberrations and clinical outcomes. This further classification could be helpful to refine prognostication and potentially provide risk stratification for treatment planning. AIM: To interrogate archival medulloblastoma samples using Oncoscan Microarray Assay, correlate with clinical features and consider the assay for clinical use. METHODS: Thirty-one archival samples with histological diagnosis of medulloblastoma and molecular grouping results from NanoString were retrieved and evaluated with Oncoscan Microarray Assay. Twenty-six were subjected to DNA methylation profiling to compare the results. Eight cases also had molecular data from next-generation sequencing (NGS) done with the in-house Ampliseq Childhood Cancer Panel. Correlation was made with clinical characteristics and outcomes of these 31 patients. RESULTS: OncoScan microarray showed distinct differences in the copy number profiles of the 31 medulloblastoma samples. Seventeen samples could be further classified into one of 12 subgroups. However, further subgrouping was challenging without first determining the main molecular group especially amongst non-WNT/SHH tumours. DNA methylation results provided corroboration with the Oncoscan subgrouping results in 25 of 26 samples. NGS panel detected additional genetic alterations in 5 of 8 samples. CONCLUSIONS: Oncoscan Microarray Assay showed potential in providing additional molecular information for further subgrouping of medulloblastoma, but was insufficient for determining the main molecular groups. Moving forward, molecular characterization could instead be done through use of NGS panel and DNA methylation, which provides tumour epigenetic profiling on top of copy number variants. These could be used alongside the NanoString platform, which is performed routinely for all medulloblastomas at our centre.